Evaluación de Metodos de Producción de Plántulas de Pumamaqui (oreopanax ecuadorensis), en el Vivero Experimental CEASA de la Universidad Técnica de Cotopaxi, 2019. - Tapia Martínez, Joselyn Dayana (2019)
The present investigation was carried out with the objective of evaluation three germination methods of the native Pumamaqui species, since it has an environmental interest, this was executed for the knowledge of the propagation of the species of puma maqui (Oreopanax ecuadorensis), with the intention to recognize which method is suitable for the realization of it, through this project the study of the native species was applied: Pumamaqui., by means of three germination methods: chemical method, physical method and control. The variables that were evaluated during the execution of the research project were: germination percentage during 20 and 30 days, plant height at 20, 30, 60, 90 and 120 days and the number of leaves of 60 and 120 days. The results were analyzed using the YUPANA software, the Tukey test was performed; and it was determined when analyzing the germination percentage variable, the best germination method was determined in the pumamaqui (Oreopanax Ecuador) is the chemical method (e1m1) with 47.62% at 30 days the relationship between 20 years 30 days after planting we obtained an existence of -08 ***. The best method in the variable height of the plant at 120 days is the physical method (e1m2) with a significant height of 0.00107 **. The variable number of leaves does not maintain a significance since it is 0.743 being this a high value.